Vocational training and gender-specific development of income in West-Germany : examples of horizontal and vertical segregation during the first years of employment - Engelbrech, Gerhard [Verfasser]; Beckmann, Petra [Herausgeber] (My University, 1996)
The Bundesantalt für Arbeit's employment statistics reveal that despite changes in demand and supply on the labour market in the eighties, the differences in incomes earned by men and women with apprenticeship vocational training persisted. Both in the eighties and the nineties men earned about 25 per cent more when starting their vocational careers than women with similar training. Such differences in income are mainly due to gender-specific segregation in better-paid male-dominated and lower-paid female-dominated occupations. But even though they have the same training, young men will earn more than young women in their first job. As the proportion of women in traditionally male-dominated or mixed occupations increased in the eighties the gap of gender-specific income differences narrowed. At the same time typical female occupations were downgraded - when compared to average incomes, which meant a contrary development. Within the occupational fields the income differences between men and women became more pronounced in the course of their careers. The difference in income levels between male, female and mixed occupations narrowed, though. Which means that the human capital investments in female occupations are upgraded compared with male occupations in the course of a longer career, which reduces horizontal segregation. In contrast with this, vertical segregation makes gender-specific discrimination more pronounced in the course of a longer career history. (author's abstract)
Keywords: G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; P 2 Zielgruppen nach Bildungsstatus; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; I 2.1.2 Alte Bundesländer; Einkommensunterschied; Geschlechtsspezifische Faktoren; Betriebliche Berufsausbildung; Absolvent; Berufsanfänger; Segregation; Männerberuf; Frauenberuf; Berufsverlauf; Diskriminierung; Quantitative Angaben; Westdeutschland; 1980-1990